Assessing Quality of Life among Radiation-Induced Hypopituitary Patients - Ryder, C Yoonhee; Bellile, Emily L.; VanKoevering, Kyle K.; McKean, Erin L. (Journal of Neurological Surgery Part B: Skull Base, 2022)
Introduction Radiation-induced hypopituitarism (RIH) has long been recognized as one of the deleterious side effects of skull base radiation. This study aims to assess the quality of life (QoL) among patients with RIH compared with radiated patients who did not develop hypopituitarism using the validated Anterior Skull Base Questionnaire (ASBQ).Methods This was a single-institution retrospective cohort study. Included patients had a history of anterior skull base tumor, underwent at least one round of radiation to the skull base, and had filled out at least one ASBQ survey after their radiation treatment. Three statistical models were used to determine the effect of hypopituitarism and treatment on QoL scores.Results A total of 145 patients met inclusion criteria, and 330 ASBQ surveys were analyzed. Thirty-five percent (51/145) had evidence of RIH at some point after their radiation treatment. Those with hypopituitarism had significantly lower overall ASBQ scores across all three models even after adjusting for potential confounders and intraperson correlation (average decrease of 0.24–0.45 on a 5-point Likert scale; p-values ranging from 0.0004 to 0.018). The increase in QoL with hormonal replacement was modulated by time out from radiation, with long-term survivors (5+ years out from radiation) gaining the most benefit from treatment (increase of 0.89 on a 5-point Likert scale, p 0.0412), especially in the vitality domain.Conclusion This data demonstrates that hypopituitarism is an independent predictor of lower QoL. Early detection and appropriate treatment are essential to avoid the negative impact of hypopituitarism on QoL.
Keywords: sinonasal malignancies; radiation side effects; radiation-induced hypopituitarism; hypopituitarism screening; quality of life; Anterior Skull Base Questionnaire